Perancangan Aplikasi Perangkat Lunak Penghapus Folder Dengan Menggunakan Algoritma Network Security Agency (NSA) - Ritonga, Samsul Malik (JURIKOM (Jurnal Riset Komputer), 2019)
Along with technological advances in various fields, as if there was never a death to learn it. From day to day technological advances continue to develop very rapidly which greatly affects human work and much of human work itself has been replaced by computer technology. On the Windows operating system, when deleting a file, the file is not completely erased. This file is only hidden by "bleaching" the cluster where the file is located. This file can be called back using a special application that can read the location of the file. This can harm the computer user. If the data deleted is data that should not be known to others, then the file must be completely lost from the data storage media. To overcome this problem, it can be used for secure data deletion in the data storage media cluster. The algorithm that can be used to delete a folder is the NSA (Network Security Agency). The NSA method is a method for deleting data by "bleaching" the data seven times. With seven times of data bleaching, this method is very suitable for safe erasing of data with very little chance of being recovered